Thymomatous myasthenia gravis: 10‐year experience of a single center. (6th September 2020) - Chen, Jiaxin; Shang, Wenjin; Chen, Yin; Li, Yan; Huang, Xin; Su, Chunhua; Zhu, Kai; Zhang, Jieni; Liu, Weibin; Feng, Huiyu
Abstract : Objectives: To summarize the clinical features of thymomatous myasthenia gravis (T‐MG), examine the association between MG and thymoma, and identify the related factors or predictors for long‐term prognosis of T‐MG. Methods: A retrospective, observational study was conducted on 100 patients with T‐MG and 96 patients with non‐T‐MG (NT‐MG) between January 1, 2009 and December 31, 2019. The baseline characteristics were recorded for each patient. Logistic regression was used to measure the association between all clinical variables and T‐MG prognosis. Results: Between the T‐MG and NT‐MG groups, age at onset (45.66 ± 11.53 years vs 39.06 ± 14.39 years); age >40 years (72.0% vs. 40.6%); AChR‐Ab positive rate (100.0% vs. 83.3%); Myasthenia Gravis Foundation of America (MGFA) classification at the worst condition (≥grade III, 61.0% vs. 33.0%); thyroid dysfunction (7.0% vs. 20.8%); and outcome (complete stable remission + pharmacologic remission + improvement, 74.0% vs. 93.7%) were statistically significant ( P  < .05). Presence of thymoma (OR = 0.196, 95%CI = 0.076‐0.511, P  = .001) was a risk factor for MG. Male sex, post‐operative complications, higher grade of MGFA classification, and thymoma Masaoka‐Koga pathological stage were risk predictors for long‐term prognosis of T‐MG ( P  < .1). Use of preoperative anticholinesterase drugs (OR = 5.504, 95%CI = 1.424‐21.284, P  = .013) was identified as an independent predictor for T‐MG. Conclusion: T‐MG is clinically different from NT‐MG, and thymoma is considered a risk factor for MG. Preoperative anticholinesterase drug use is a protective factor for long‐term prognosis of T‐MG. A comprehensive understanding of the characteristics of T‐MG will likely help improve its prognosis.